Strategi Adaptasi Mahasiswa Pekerja Korban PHK Di Masa Pandemi Covid-19 (Studi Pada Mahasiswa Pekerja Asal Kabupaten Mamasa Di Kota Makassar) - Saul Saul; Andi Agustang; Darman Manda (Phinisi Integration Review, 2022)
This study aims to determine 1) the adaptation strategy of student workers from Mamasa Regency who were laid off victims in Makassar City, 2) What factors influenced the adaptation strategy of student workers from Mamasa Regency who were laid off victims in Makassar City. The type of research used is qualitative research with a case study method or approach to describe the adaptation strategy of student workers from Mamasa Regency who are victims of layoffs in Makassar City. The technique of determining the informants was done by purposive sampling technique with the criteria of informants, namely student workers who were laid off and had worked for more than one year, totaling 10 people. Data collection techniques are observation, interviews, and documentation. The data validation technique uses source triangulation.The results of this study indicate that 1) Student workers from Mamasa Regency, victims of layoffs in Makassar City have several strategies in meeting their daily needs, including a) Leave from college, b) Go home, c) Save expenses, d) Switch jobs (become an online motorcycle taxi driver). and day laborers). 2) There are three factors that influence the adaptation strategy of student workers from Mamasa Regency who are victims of layoffs in Makassar City, namely a) Socio-economic conditions of the family, b) Peer Group / circle of friends, c) Skill / skills.